Thermal conductivity of cryoprotective agents loaded with nanoparticles, with application to recovery of preserved tissues and organs from cryogenic storage - Lili E. Ehrlich; Zhe Gao; John C. Bischof; Yoed Rabin; Fankang Li (PLoS ONE, 2020)
The objective of this study is to provide thermal conductivity data for CPA-based nanofluids for the benefit of the analyses of cryopreservation by vitrification. Thermal conductivity measurements were conducted using a hot-wire technique on an experimentation platform of the cryomacroscope, to correlate measurements with observed physical effects such as crystallization and fracturing. Tested materials in this study include the CPA cocktails M22, VS55, DP6, and DP6+sucrose. Nanofluids in this study include the above CPA cocktails as base solutions, when mixed with either iron-oxide nanoparticles (IONP) or silica-coated iron-oxide nanoparticles (sIONP). Results of this study demonstrated the addition of sIONP to any of the CPA cocktails tested did not significantly affect its thermal conductivity, its tendency to vitrify or, conversely, its tendency to form rewarming phase crystallization (RPC). Fractures were observed with cryomacroscopy at the onset of rewarming for DP6+sIONP under carefully controlled rewarming conditions without RF activation, despite the inherent opacity of the sIONP solutions. It is likely that using RF heating in order to accelerate rewarming while unifying the temperature distribution would prevent fracture and RPC. However, sIONP were not activated in this study, as the RF heating mechanism would interfere with thermal conductivity measurements. The addition of IONP to DP6 appears to hinder the tendency of the CPA to vitrify, which is a detrimental effect. But it is unlikely that uncoated nanoparticle solutions will be used in practical applications.